(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
Anorexia nervosa is a potentially fatal disorder with low insight unto the consequences of persisting lack of food intake. Hence, it may need sometimes involuntary hospitalisation to avoid severe medical complications and death. The draft bill, that intends to introduce a compulsory treatment in anorexia, is controversial and costly, putting constitutional rights, such as freedom and health, on the line. This paper focuses on the legal and ethical debate concerning involuntary hospitalization of treatment-resistant anorexia patients, considering this option not so much as an ultimate remedy to a chronic illness, but rather as a last resort life-saving measure. In cases as these, when we come to recognize the challenges in defining a psychiatric illness like anorexia nervosa for the purposes of deciding whether invol-untary treatment laws can be invoked, we begin to appreciate the high stakes at this intersection between law and psychiatry.